2016
DOI: 10.1016/j.cub.2016.10.051
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic compass that might help coral reef fish larvae return to their natal reef

Abstract: Many coral reef fish larvae spend days to months in the open ocean before settlement on coral reefs [1]. Early in development, larvae have limited swimming capabilities and will therefore be greatly affected by currents. This can potentially result in dispersal distances of tens of kilometers [2]. Nevertheless, up to 60 % of surviving larvae have been shown to return to their natal reefs [2]. To home, the larvae must develop strong swimming capabilities and appropriate orientation mechanisms. Most late-stage l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…It was demonstrated that the O. doederleini larvae were navigating using a sun compass mechanism (Mouritsen et al, 2013) and sun compass orientation has also been documented in other coral reef fish species (e.g., Leis and Carson-Ewart, 2003;Berenshtein et al, 2014). Bottesch et al (2016) demonstrated that newly settled O. doederleini at OTI can also orient their swimming to the SE at night via a magnetic compass mechanism. In this study, it was assumed that L. carponotatus spawned from reefs in the CBG (which are affected by the same prevailing NNW current as OTI) would have a strong SSE directional swimming response like O. doederleini.…”
Section: Biophysical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…It was demonstrated that the O. doederleini larvae were navigating using a sun compass mechanism (Mouritsen et al, 2013) and sun compass orientation has also been documented in other coral reef fish species (e.g., Leis and Carson-Ewart, 2003;Berenshtein et al, 2014). Bottesch et al (2016) demonstrated that newly settled O. doederleini at OTI can also orient their swimming to the SE at night via a magnetic compass mechanism. In this study, it was assumed that L. carponotatus spawned from reefs in the CBG (which are affected by the same prevailing NNW current as OTI) would have a strong SSE directional swimming response like O. doederleini.…”
Section: Biophysical Modelingmentioning
confidence: 99%
“…In addition to physical oceanographic features, the biological characteristics of fish larvae can greatly affect their dispersion (Kingsford et al, 2002;Paris et al, 2013;Wolanski and Kingsford, 2014;Bottesch et al, 2016). The larvae of many fish species can maintain swim speeds that exceed local mean current speeds for extended periods of time, they can, therefore, influence their dispersal trajectories (Fisher, 2005;Leis, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there is no empirical information about a common swimming directions of larvae in the GoA (in contrast to other locations, e.g., Bottesch et al, 2016), but using the axial direction of the GoA makes biological sense since it minimizes the coastal encounters of the larvae, and therefore minimizes their risk of predation. Kappa values for BCRW individual larvae were estimated from the experimental data of Irisson et al (2015) (see explanation in CRW section above) resulting in kappa = 1.…”
Section: Biased-correlated Directional Swimming (Bcrw)mentioning
confidence: 99%
“…Larvae can swim in an orientated way at speeds that are often comparable to the currents of the waters in which they live, thus directly influencing their dispersal. Larvae can detect and respond to a range of olfactory, auditory, and visual cues from settlement habitat, from within the pelagic environment (Leis et al, 2011b) and even to celestial (Mouritsen et al, 2013;Leis et al, 2014) and magnetic (Bottesch et al, 2016;O'Connor and Muheim, 2017) cues. By controlling their vertical distribution, larvae may indirectly influence their dispersal because current velocities often vary with depth.…”
Section: Introductionmentioning
confidence: 99%